2010
DOI: 10.1192/pb.bp.109.025684
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of deprivation of liberty: a survey of in-patient services

Abstract: Aims and methodA trust-wide survey of all in-patients to estimate the prevalence of likely deprivation of liberty and to investigate how two different approaches to measuring deprivation might affect the number identified.ResultsA notable difference in the results was detected when comparing the two methods. One survey method identified deprivation of liberty factors in 84% of informal incapacitous patients, whereas a different approach that weighed up the factors in accordance with the UK government's interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Managers' understanding of the complexity of the issue was limited; the authors quoted one respondent baldly asserting, 'Deprivation of liberty speaks for itself ' (p. 290). Selmes, Roninson, Mills, Branton, and Barlow (2010) reviewed the circumstances of 55 informal mental health and learning disability patients in one health trust. Defining a DoL in terms of the presence of at least one significant safeguarding factor, 46 of these patients were being deprived of their liberty, mainly because the staff would prevent the person from taking their own discharge.…”
Section: Previous Researchmentioning
confidence: 99%
“…Managers' understanding of the complexity of the issue was limited; the authors quoted one respondent baldly asserting, 'Deprivation of liberty speaks for itself ' (p. 290). Selmes, Roninson, Mills, Branton, and Barlow (2010) reviewed the circumstances of 55 informal mental health and learning disability patients in one health trust. Defining a DoL in terms of the presence of at least one significant safeguarding factor, 46 of these patients were being deprived of their liberty, mainly because the staff would prevent the person from taking their own discharge.…”
Section: Previous Researchmentioning
confidence: 99%
“…Shah and Heginbotham (2010) argue that this absence of an agreed legal definition of deprivation of liberty -and potential confusion with the less coercive "restriction" of liberty -creates difficulties for practitioners in determining what constitutes the threshold for deprivation of liberty. While the DoLS Code of Practice (Ministry of Justice, 2008) states "there is no simple definition of deprivation of liberty", Selmes et al (2010) assert that this raises questions about how to decide who will require a DoLS assessment.…”
Section: No Legal Definition Of Deprivation Of Libertymentioning
confidence: 99%
“…The lawyers' expert views were based on current available case law, but they represented a divergence from Code of Practice guidance on DoLS. Selmes et al (2010) state that clinicians are anxious about being asked to apply a legal concept that has emerged from ad hoc case law into real-life clinical situations. Their study demonstrated the difficulty of clearly defining deprivation of liberty, and claimed further case law could lead to a dramatic change in deprivation of liberty prevalence.…”
Section: No Legal Definition Of Deprivation Of Libertymentioning
confidence: 99%
“…Thus a person's personal conviction system is part of their personal history and identity. When George Kelly 3 developed the personal construct theory he demonstrated that everyone has a personal template by which they evaluate life. If we seek to understand and respect this, we discover that we will need also to look at our own understanding because we in turn evaluate others on the basis of our own templates.…”
mentioning
confidence: 99%